Observing complex social territories - SITEC, Equipo (Critical Proposals in Social Work, 2023)
Understanding the territory as a complex system implies paying attention to the emergence of new phenomena that arise from the interaction between social and environmental elements in delimited contexts. In this sense, objective, temporal and communicational dimensions converge in the territory. objective, temporal and communicational dimensions converge in the territory, from which it acquires its own form. The observation of the territory, therefore, implies identifying spatial or geographical limits; past and present decisions from which future expectations are projected; thematizations of problems, conflicts and controversies arising from the positions of different agents and institutions. On the other hand, each territory represents a particular context in which universal phenomena are expressed with their own logics. This issue of the Journal Propuestas Críticas en Trabajo Social integrates different territorial studies and analyses in which it is possible to identify intervention strategies and proposals that emerge both from second-order observation processes and from the self-observation that the actors of the territories make of their problems and their relationship with the environment. The works presented address different problems that, in addition, come from territories in different regions of Chile, evidencing the spatial and cultural spatial and cultural limits of this type of systems.